Western Balkans (7th–14th c.) – Lost and Restored to Byzantium - Dudek, Jarosław (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The article is devoted to Western Balkans (territories to the north of the old Byzantine-Bulgarian border, west to the coasts of Ionian Sea and Adriatic, east to the Strymon valley, south to Hungary and Serbia) in the period from the 11th to the 15th c.